Zero Constant Mean Curvature Surface Family in Minkowski Space - Kahyaoglu, Sedat; Kasap, Emin (Editura Bibliotheca-Bibliotheca Publ House, 2016)
We study zero constant mean curvature surface family prescribed by a given curve in Minkowski 3-space. We derive necessary and sufficient condition for zero constant mean curvature surface family prescribed a timelike or spacelike curve. We indicate the condition of a given curve is a geodesic curve or asymptotic curve on zero constant mean curvature surfaces.
Keywords: Constant Mean Curvature Surface; Spacelike Maximal Surface; Timelike Minimal Surface; Frenet Frame